Mesenchymal stem cell-derived extracellular vesicles as a cell-free therapy for traumatic brain injury via neuroprotection and neurorestoration - Xiong, Ye; Mahmood, Asim; Chopp, Michael (Neural regeneration research, 2024)
Traumatic brain injury is a serious and complex neurological condition that affects millions of people worldwide. Despite significant advancements in the field of medicine, effective treatments for traumatic brain injury remain limited. Recently, extracellular vesicles released from mesenchymal stem/stromal cells have emerged as a promising novel therapy for traumatic brain injury. Extracellular vesicles are small membrane-bound vesicles that are naturally released by cells, including those in the brain, and can be engineered to contain therapeutic cargo, such as anti-inflammatory molecules, growth factors, and microRNAs. When administered intravenously, extracellular vesicles can cross the blood-brain barrier and deliver their cargos to the site of injury, where they can be taken up by recipient cells and modulate the inflammatory response, promote neuroregeneration, and improve functional outcomes. In preclinical studies, extracellular vesicle-based therapies have shown promising results in promoting recovery after traumatic brain injury, including reducing neuronal damage, improving cognitive function, and enhancing motor recovery. While further research is needed to establish the safety and efficacy of extracellular vesicle-based therapies in humans, extracellular vesicles represent a promising novel approach for the treatment of traumatic brain injury. In this review, we summarize mesenchymal stem/stromal cell-derived extracellular vesicles as a cell-free therapy for traumatic brain injury via neuroprotection and neurorestoration and brain-derived extracellular vesicles as potential biofluid biomarkers in small and large animal models of traumatic brain injury.